Study on spalling behaviours of the railway wheel steel - Chen, Weiquan (2019)
The objective of this paper is to investigate the spalling behaviours of the railway wheel steel. This concern the safety of the passenger commuting via train and it is important for us to understand what potential failure it might occur. One such potential failure is known as spalling. Spalling is often associate with rolling contact fatigue (RCF). Rolling-contact fatigue well-known to be found on railway wheel contact. Propagation of crack found in the railway wheel is often initiated in a layer known as White Etching Layer (WEL). The crack might propagate enough to break part of the material and leaving empty spaces which is term as spalling. This phenomenon is caused by cyclic rolling contact experienced by the wheel. Software tools that uses finite element analysis like Abaqus is used to study the effect of spalling. The primarily focus in this investigation is to find out the effects of different crack angles and loading at the surface of the white etching layer subjected to direct cyclic loading. The 2D simulation is discretized using extended finite element which is within the frame work Abaqus Version 6.13. The software program allows for simulation of crack growth and propagation within the WEL layer.